Coins of Ukraine with mammalian images - Igor Zagorodniuk (Theriologia Ukrainica, 2019)
The history of coins with images of mammals in Ukraine is reviewed. Since 1998, 22 coins have been issued (excluding the silver and nickel silver), which form 5 series. The principal ones are the "Flora and Fauna series" (including Nature Reserve Fund objects) and "Fauna in Cultural Monuments of Ukraine", nevertheless fauna objects are presented in several other series. In particular, mammals are featured in the series "Various" (e.g., "Year of Bat"), "The Smallest Gold Coin" (e.g., "Marmot", "Hedgehog", and "Boar" and "Deer" in sub-series "Scythian Gold") and "Monuments of Ancient Cultures of Ukraine" (picture Scythian deer in sub-series "Scythia"). The zoological accuracy of the images, the series' similarity with series from other countries (e.g., Belarusian coins depicting bison, Russian coins with images of sand mole-rat and other rare species) and the issue dynamics, which has a slight tendency to increase in number of coin types, are analysed.